Biogenic synthesis of silver nanoparticles using Rubus fruticosus extract and their antibacterial efficacy against Erwinia caratovora and Ralstonia solanacearum phytopathogens - Khan, Adnan; Ahmad, Nisar; Fazal, Hina; Ali, Mohammad; Akbar, Fazal; Khan, Ishaq; Tayyab, Mohammad; Uddin, Muhammad Nazir; Ahmad, Naveed; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Zomot, Naser; et al. (Royal Society of Chemistry (RSC), 2024)
In the current research, we produced green, cost-effective, eco-friendly silver nanoparticles using a single-step approach. Plants are considered highly desirable systems for nanoparticle synthesis because they possess a variety of secondary metabolites with significant reduction potential. In the current research, the dried leaf extract of Rubus fruticosus was utilized as a capping and reducing agent for the fabrication of silver nanoparticles, to prepare reliable biogenic silver nanoparticles and subsequently to investigate their potential against some common phytopathogens. The prepared silver nanoparticles were exploited to quantify the total flavonoid content (TFC), total phenolic content (TPC) and DPPH-based antioxidant activity. Different concentrations of aqueous extracts of plant leaves and silver nitrate (AgNO3) were reacted, and the color change of the reactant mixture confirmed the formation of Rubus fruticosus leaf-mediated silver nanoparticles (RFL-AgNPs). A series of characterization techniques such as UV-vis spectroscopy, transmission electron microscopy, energy dispersive X-ray analysis and X-ray diffraction revealed the successful synthesis of silver nanoparticles. The surface plasmon resonance peak appeared at 449 nm. XRD analysis demonstrated the crystalline nature, EDX confirmed the purity, and TEM demonstrated that the nanoparticles are mostly spherical in form. Furthermore, the biosynthesized nanoparticles were screened for in vitro antibacterial activity, antioxidant activity, and total phenolic and flavonoid content. The nanoparticles were used in different concentrations alone and in combination with plant extracts to inhibit Erwinia caratovora and Ralstonia solanacearum. In high-throughput assays used to inhibit these plant pathogens, the nanoparticles were highly toxic against bacterial pathogens. This study can be exploited for planta assays against phytopathogens utilizing the same formulations for nanoparticle synthesis and to develop potent antibacterial agents to combat plant diseases.